Pengaruh Corporate Social Responbility (CSR) Terhadap Tax Avoidance - Icha Sendina; Eny Wuryani (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2021)
This study aims to determine the effect of corporate social responsibility on tax avoidance. The population used is mining companies listed on the Stock Exchange in 2014-2018 with a sampling method that is purposive sampling with a sample obtained by 49 companies used. Research used quantitative research and used secondary data in the form of financial statements in this sector. The measurement used in this study is the Cash Effective Tax Rate (CETR) for tax avoidance while the Log (cost) for corporate social responsibility uses simple linear regression. The results show that there is no effect of corporate social responsibility on tax avoidance.